Factors Affecting the Capacity of Green Gang Managers in the Utilization of Yards for Green Open Space in Jakarta - Suryani; Muljono, Pudji; Susanto, Djoko; Harijati, Sri (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2021)
This study aims to identify the Green Gang Manager capacity level and analyze the factors that affect the Green Gang Manager capacity in Jakarta. The technique of research includes a survey approach for 340 respondents in DKI Jakarta Province from 2,236 Green Gang Managers. Research in the five administrative towns of central Jakarta, East Jakarta, West Jakarta, South Jakarta and North Jakarta has been undertaken between December 2019 and February 2020. Techniques for data collecting through open interviews, in-depth interviews and focus group discussions. Inferential data analysis. Data analysis. PLS and Logical model analysis using Structural Equation Modeling (SEM). The results showed that the capacity of Green Gang Managers in DKI Jakarta Province was in the medium category. This indicates that the Green Alley Manager's capacity level is quite understanding regarding utilizing Green Open Space. Green Gang Managers' ability is influenced significantly and effectively by individual properties, support of stakeholders and Green Gang managers' involvement. Non-formal training and motivation are personal attributes that affect Green Gang Manager skills. The role of the government, the part of the community, the role of the media and the role of extension workers are all stakes that influence the capacity of the Green Gang manager. Planning, implementation, using outcomes and evaluation are the level of participation that influences the capacity of Green Gang managers.